The Old Czech and Middle Czech Nouns with the Suffix -ež and Their Word-Formative Development - Šimek, Štěpán (Bohemica Olomucensia, 2016)
The article focuses on the Old Czech and Middle Czech nouns with the suffix -ež and their word-formative development. Unproductiveness of this word-forming type and peripheral character of lexical items derived within it is proved even in older stages of Czech.
Keywords: language development; diachrony; Old Czech; Middle Czech; word-formation; suffix; productiveness